Syntheses and Antibacterial Activity of Testosterone Succinate-Vitamin B1 Conjugate - Figueroa-Valverde, L.; Díaz-Cedillo, F.; Camacho-Luis, A.; Lopez-Ramos, M. (Asian Journal of Chemistry, 2010)
In this study, a straight forward route for the synthesis of testosterone succinate-vitamin B1 conjugate and their antibacterial activities on S. aureus, E. coli and K. pneumoniae are reported. This first step was achieved by reacting 3-[(4-amino-2-methyl-5-pyrimidinyl)methyl]-5-(2- hydroxyethyl)-4-methylthiazolium chloride (vitamin B1) with testosterone-succinate resulting in amide bond formation. The results showed that the 1H NMR spectra of the testosterone succinate- vitamin B1 conjugate shows upfield shifts at 0.80 and 1.19 ppm for methyls present in the heterocyles rings at 3.18 and 3.90 ppm for methylenes of the hydroxietilen moiety bonded to thiazol ring. The hydrogens of the methylene between the pyrimidine and thiazol rings appears at 5.68 ppm. In addition, the proton of methyl bound to pyrimidine ring at 5.69 ppm was found. The antibacterial activity of testosterone succinate-vitamin B1 conjugate on S. aureus, K. pneumoniae and E. coli was evaluated by means of dilution method and the minimum inhibitory concentration (MIC). The results showed that bacterial growth of S. aureus was blocked in presence of the steroid-derivative (MIC = 2.57 × 10-3 mmol). In addition, the bacterial growth of E. coli and K. pneumoniae in presence of testosterone succinate-vitamin B1 conjugate (MIC = 1.48 × 10-3 mmol) was blocked. The experimental data suggest that quaternary amine group involved in the testosterone succinate-vitamin B1 conjugate require only positive charge together with a hydrophobic region, in order to interact with the cell surface and perturb bacterial growth.